Get personalized answers to your unique questions on IDNLearn.com. Get accurate and detailed answers to your questions from our knowledgeable and dedicated community members.
Sagot :
To solve the problem of finding \( f(3) + f(2) \) using the given table, let's walk through the steps carefully:
1. Identify \( f(3) \):
- We look at the row corresponding to \( f(x) \).
- Find the value of \( f(x) \) when \( x = 3 \):
[tex]\[ f(3) = 1 \][/tex]
2. Identify \( f(2) \):
- Again, we refer to the same row for \( f(x) \).
- Find the value of \( f(x) \) when \( x = 2 \):
[tex]\[ f(2) = 3 \][/tex]
3. Calculate \( f(3) + f(2) \):
- Add the values we found:
[tex]\[ f(3) + f(2) = 1 + 3 \][/tex]
4. Determine the result:
- The final calculation yields:
[tex]\[ f(3) + f(2) = 4 \][/tex]
Thus, the value of [tex]\( f(3) + f(2) \)[/tex] is [tex]\( 4 \)[/tex].
1. Identify \( f(3) \):
- We look at the row corresponding to \( f(x) \).
- Find the value of \( f(x) \) when \( x = 3 \):
[tex]\[ f(3) = 1 \][/tex]
2. Identify \( f(2) \):
- Again, we refer to the same row for \( f(x) \).
- Find the value of \( f(x) \) when \( x = 2 \):
[tex]\[ f(2) = 3 \][/tex]
3. Calculate \( f(3) + f(2) \):
- Add the values we found:
[tex]\[ f(3) + f(2) = 1 + 3 \][/tex]
4. Determine the result:
- The final calculation yields:
[tex]\[ f(3) + f(2) = 4 \][/tex]
Thus, the value of [tex]\( f(3) + f(2) \)[/tex] is [tex]\( 4 \)[/tex].
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.